Green preparation and enhanced gas barrier property of rubber nanocomposite film based on graphene oxide-induced chemical crosslinking. (26th May 2021) - Wang, Linyan; Zhang, JiangTao; Sun, Youyi; Zhang, Tao; Wang, Long; Wang, Jian; Liang, Yurong; Hao, Mingzheng; Fu, Qiang
Abstract: A green and facile preparation method of graphene oxide/nitrile butadiene rubber (GO/NBR) nanocomposite film was developed for application in gas barrier. In the process, chemical crosslinks were formed by graphene oxide (GO)-induced crosslinking in absence of vulcanization ingredients. It was found that the GO-induced crosslinking occurred at a higher concentration of 1.0 wt% and a higher temperature of 170.0 °C. The GO-induced crosslinking did not only enhance the crosslinking density of GO/NBR nanocomposite film, but also enhanced interfacial interactions between GO and NBR matrix. The resultant GO/NBR nanocomposites with 3.0 wt% GO loading displayed enhanced tensile strength by ~145% as well as exhibited a dramatically decreased gas permeability coefficient by ~56% compared to the pristine NBR. The excellent comprehensive performance of GO/NBR nanocomposites was attributed to good barrier and high mechanical property of GO. In addition, the strong interfacial interaction between GO and NBR was also key role for enhancing tensile strength and barrier of GO/NBR nanocomposites. This 'green' and facile method provides new insights for the fabrication of high-performance GO/rubber composites for various applications. Graphical abstract: Image 1 Highlights: A green GO-induced crosslinking of rubber was developed. Segregated GO/NBR composite film were prepared by in-situ latex method. The film exhibited excellent interfacial interaction and gas barrier property.